2020
DOI: 10.1111/jgh.15041
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, clinical course, and predictive factors of immune checkpoint inhibitor monotherapy‐associated hepatitis in Japan

Abstract: Background and Aim: Immune checkpoint inhibitors (ICI) have revolutionized anti-malignancy therapy and thus have been increasingly used. Although ICI may cause immune-related adverse events (irAE) in various organs, including the liver, the prevalence and predictive factors of irAE have not been clarified. Methods: In this retrospective study, consecutive patients who had malignancies and were treated with ICI without other chemotherapeutic agents at Hokkaido University Hospital between 2014 and 2019 were scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 27 publications
(43 reference statements)
6
29
0
Order By: Relevance
“…Few studies have assessed the differences in clinical characteristics of immune-related liver injury between multisystem and single irAEs. We found that immune-related liver injuries in multisystem irAEs occurred later than those in cases with liver irAEs alone, and the use of the anti-CTLA-4 antibody was associated with the incidence of multisystem irAEs, consistent with previous reports 23,24 . Our study demonstrated that the common types of irAEs accompanying liver injury were endocrine and GI injuries.…”
Section: Discussionsupporting
confidence: 91%
“…Few studies have assessed the differences in clinical characteristics of immune-related liver injury between multisystem and single irAEs. We found that immune-related liver injuries in multisystem irAEs occurred later than those in cases with liver irAEs alone, and the use of the anti-CTLA-4 antibody was associated with the incidence of multisystem irAEs, consistent with previous reports 23,24 . Our study demonstrated that the common types of irAEs accompanying liver injury were endocrine and GI injuries.…”
Section: Discussionsupporting
confidence: 91%
“…In a study from Oxford, 19/21 patients (90.5%) with hepatotoxicity due to Check Point Inhibitors were treated with corticosteroids (Cheung et al, 2019) (Table 1), but only 50% had a treatment response, which was similar to a study from Japan (Kitagataya et al, 2020). The study by Ito et al from Japan was somewhat of an outlier showing a response to steroid treatment in only 33% of cases (Ito t al.…”
Section: Steroid Use In Check Point Inhibitor Induced Liver Injurysupporting
confidence: 62%
“…Thus, our results fit very well to what is known. Furthermore, Kitagataya et al [ 20 ] reported an association between female sex and autoimmune hepatitis under immunotherapy. However, the underlying pathomechanism is not fully understood yet.…”
Section: Discussionmentioning
confidence: 99%